2013
DOI: 10.3390/agronomy3020313
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Impacts on Soil Physical Properties and Greenhouse Gas Emissions

Abstract: Biochar, a co-product of a controlled pyrolysis process, can be used as a tool for sequestering C in soil to offset greenhouse gas (GHG) emissions, and as a soil amendment. Whereas the impacts of biochar application on soil chemical properties are widely known, the research information on soil physical properties is scarce. The objectives of this review are to (i) synthesize available data on soil physical properties and GHG emissions, (ii) offer possible mechanisms related to the biochar-amended soil processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
268
3
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(306 citation statements)
references
References 130 publications
24
268
3
11
Order By: Relevance
“…The specific soil-BC combination affects amended soil properties Camps-Arbestain et al, 2015). In fact, several authors have shown that BC amendment can positively modify the physical, chemical, and biological properties of soil (Barrow, 2012;Mukherjee and Lal, 2013;Subedi et al, 2016b;Schmalenberger and Fox, 2016).…”
Section: Biochar Effects On Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific soil-BC combination affects amended soil properties Camps-Arbestain et al, 2015). In fact, several authors have shown that BC amendment can positively modify the physical, chemical, and biological properties of soil (Barrow, 2012;Mukherjee and Lal, 2013;Subedi et al, 2016b;Schmalenberger and Fox, 2016).…”
Section: Biochar Effects On Soil Propertiesmentioning
confidence: 99%
“…The positive effects of amending the soil with BC include increased crop productivity and soil fertility (Liu et al, 2013(Liu et al, , 2014Windeatt et al, 2014;Biederman and Harpole, 2013;Jeffery et al, 2011Jeffery et al, , 2015b mainly through improved quality, C storage, infiltration, and water holding capacity of soil (Mukherjee and Lal, 2013;Mukherjee et al, 2014). Compared to other amendments, BC is thought to be C-negative because it is derived from atmospheric CO2 captured by plants, which is then diverted to the soil in a very stable form where it can remain for several years (Lehmann and Joseph, 2015;Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has identified several environmental and agricultural benefits of applying biochar, including carbon sequestration for reducing carbon emission into the atmosphere (Mašek et al, 2013;Mukherjee and Lal, 2013;Zhang and Ok, 2014;Jiang et al, 2016;Wang et al, 2016); phytoremediation of soil contaminants (Ahmad et al, 2014;Mohan et al, 2014;Wiszniewska et al, 2016); adjusting soil physicochemical and biochemical properties for agriculture (Herath et al, 2013;Githinji, 2014;Bai et al, 2015;Abujabhah et al, 2016;Bera et al, 2016;Haider et al, 2017); creating soil health by inducing growth of beneficial and suppressing pathogenic organisms (Lone et al, 2015;Abujabhah et al, 2016;George et al, 2016;Xu et al, 2016); and improving crop growth and yield (Vaccari et al, 2015;Agegnehu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil, China, India and USA; Fig. 3) are interested in offsetting and reducing greenhouse gas emission from agriculture by using biochar (FAO 2012;Laird 2008;IPCC 2000;Cayuela et al 2010;Mukherjee and Lal 2013). Notably, these four countries emitted in 2009 about 51% (i.e.…”
Section: Influence Of Ghg Emission On Biochar Researchmentioning
confidence: 99%
“…How biochar affect soil properties and plant performance has been reasonably assessed (Crane-Droesch et al 2013;Jeffery et al 2011;Sohi et al 2010;Liu et al 2013). Many investigations have shown that the application of biochar to soil influences soil physico-chemical properties and improves soil functions such as water and nutrient holding capacity (Crane-Droesch et al 2013;Mukherjee and Lal 2013;Ajayi and Horn 2016;Jeffery et al 2011;Haider et al 2016). These characteristics make biochar, applied alone or as its mixture with other organic amendments (e.g.…”
Section: Introductionmentioning
confidence: 99%